Capital market development, corporate governance and the credibility of exchange rate pegs - Olli Castrén; Tuomas Takalo (European Central Bank (ECB), 2000)
Focusing on emerging market currency arrangements, we build a model of an exchange rate peg with escape clauses and output persistence. We first show how output persistence works as an additional 'fundamental' so that an exogenous increase in persistence can make the currency peg more vulnerable to speculative attacks. We then endogenise output persistence as arising from capital market frictions that are caused by weak corporate governance institutions. It turns out that in emerging market economies, often characterised by credit constraints, a partial reform of corporate governance institutions may enhance a financial accelerator mechanism, which increases output persistence and deteriorates the credibility of the exchange rate peg. A conservative policymaker partially counters this adverse effect, but only a complete reform of corporate governance institutions fully eliminates persistence and reduces the risk of currency crisis on all levels of policy preferences.
Keywords: E58; F33; D84; G18; G38; 330